Computer simulation modelling of the influence of drafting on collective behaviour in an elite 10km competitive running event - Renfree, A.; Trenchard, H.; Peters, D. M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Drafting in cycling has been shown to influence the collective behaviour of pelotons during competition (Trenchard, 2015). Whilst some evidence for collective behaviour in competitive running events exists (Hanley, 2015), it is not clear as to the extent to which this is determined by energetic savings conferred by drafting. Methods: Using performance data from a men`s elite championship 10k track running event, computer simulations were constructed using Netlogo 5.1 to test the effects of three different drafting quantities on collective behaviour: no drafting, drafting to 3m behind with up to ~8% energy savings (a realistic running draft); and drafting up to 3m behind with up to 38% energy savings (a realistic cycling draft). Three measures of collective behaviour were analysed in each condition; mean speed, mean group stretch (distance between first and last placed runner), and Runner Convergence Ratio (RCR) which represents the degree of drafting benefit obtained by the follower in a pair of coupled runners. Results: Mean speed in the cycling draft condition (6.32+0.28m/s) was higher than in the other conditions, but no significant differences were found between no draft (5.51 + 0.13 m/s) and runner draft conditions (5.57 + 0.18 m/s). Likewise, RCR was lower in the cycling draft condition, but did not differ between the other two. Mean stretch did not differ between conditions. Discussion: It is suggested that collective behaviours observed in running events may not be fully explained through energetic savings conferred by realistic drafting benefits. They may therefore result from other, possibly psychological, processes.